2021
DOI: 10.3390/ma14061368
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Resistance of PP/Natural Filler Polymer Composites to Decomposition Caused by Fungi

Abstract: The article discusses the grain morphology of the natural filler from hazelnut and walnut shell flour. It was observed that the geometry of both meals is similar to each other and resembles uneven balls in shape. The heterogeneity and well-developed outer surface of the flour grains allow for filling the voids with the polymer matrix. The analysis of the surface of the SEM images allowed to observe the presence of natural filler flour grains in the entire volume of the produced polymer composites, uneven distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[33][34][35] Therefore, the use of WS in WPCs can not only partially alleviate the wood shortage in some walnut-rich countries, but also produce some benefits in the environmental and socio-economic fields. 36,37 Zheng et al 38 studied the effects of WS powder on the morphology, thermal properties, and mechanical properties of PLA. It was found that the tensile strength, impact strength, and elongation at break of PLA/WS composites increased at first and then decreased with the increase of WS powder.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Therefore, the use of WS in WPCs can not only partially alleviate the wood shortage in some walnut-rich countries, but also produce some benefits in the environmental and socio-economic fields. 36,37 Zheng et al 38 studied the effects of WS powder on the morphology, thermal properties, and mechanical properties of PLA. It was found that the tensile strength, impact strength, and elongation at break of PLA/WS composites increased at first and then decreased with the increase of WS powder.…”
Section: Introductionmentioning
confidence: 99%
“…HNS can be used for various applications such as energy, 4,5 biofuel production, 6 active carbon production, 7,8 adsorption, 9,10 waste water treatment, 11 civil engineering applications, 12,13 and polymeric composites. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In all these applications generally, it is mechanically powderized in various sizes. Since the green and sustainable material requirement is increasing, number of the research in the area of HNS filled polymer composite production has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Since the green and sustainable material requirement is increasing, number of the research in the area of HNS filled polymer composite production has been increasing. Hazelnut shells based composites were prepared by using thermoplastics such as PP, [14][15][16][17][18] polyethylene, 16,19 polylactic acid (PLA), 2,[20][21][22] polymethylmethacrylate, 23 and thermosets including epoxy, 2,[20][21][22] urea formaldehyde, 24 polyester. [25][26][27] In addition to these, HNS filled polyurethane (PU) rigid foams 28 were also reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by good mechanical properties, stiffness, ease of processing, no need for impregnation, and a relatively low price. Moreover, the use of lignocellulosic filler makes this material partially biodegradable [ 4 , 5 , 6 , 7 , 8 ]. WPCs have enormous application potential.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of lignocellulosic fibers, especially on the surface of the material, makes WPCs very susceptible to the action of microorganisms including fungi. Many works have demonstrated the negative influence of this destructive factor on the structure and properties of WPCs [ 7 , 18 , 19 , 20 , 21 ]. It has been shown that the action of fungi mainly causes the decomposition of the lignocellulosic component, which can be observed indirectly in the weight loss of the sample.…”
Section: Introductionmentioning
confidence: 99%